Answer:
x=-1 and y=-5
Step-by-step explanation:
ሰላም!
Given expressions let them given as two equations
- y=2+7x....... equation (1)
- -2x+6y=-28..... equation (2)
Thus, substitute y=2+7x into equation (2)
![- 2x + 6(2 + 7x) = - 28 \\](https://tex.z-dn.net/?f=%20-%202x%20%2B%206%282%20%2B%207x%29%20%3D%20%20-%2028%20%5C%5C%20%20)
simplify it
![- 2x + 12 + 42x = - 28 \\ 40x + 12 = - 28](https://tex.z-dn.net/?f=%20-%202x%20%2B%2012%20%2B%2042x%20%3D%20%20-%2028%20%5C%5C%2040x%20%2B%2012%20%3D%20%20-%2028)
subtract 12 from both sides
![40x + 12 - 12 = - 28 - 12 \\ 40x = - 40](https://tex.z-dn.net/?f=40x%20%2B%2012%20-%2012%20%3D%20%20-%2028%20-%2012%20%5C%5C%2040x%20%3D%20%20-%2040)
divide both sides by 40
![\frac{40x}{40} = \frac{ - 40}{40} \\ x = - 1](https://tex.z-dn.net/?f=%20%5Cfrac%7B40x%7D%7B40%7D%20%20%3D%20%20%5Cfrac%7B%20-%2040%7D%7B40%7D%20%5C%5C%20x%20%3D%20%20-%201%20)
Therefore, as we get the value of x=-1 substitute it to equation (1) and solve for variable y
![y = 2 + 7x \\ y = 2 + 7( -1 ) \\ y = 2 - 7 \\ y = - 5](https://tex.z-dn.net/?f=y%20%3D%202%20%2B%207x%20%5C%5C%20y%20%3D%202%20%2B%207%28%20-1%20%29%20%5C%5C%20y%20%3D%202%20-%207%20%5C%5C%20y%20%3D%20%20-%205)
To be more sure make a cross check on both of the two expressions
Thus,
1) y=2+7x .... substitute y=-5 and x=-1 and check if it is equal
-5=2+7(-1)
-5=2-5
-5=-5
2)-2x+6y=-28... substitute and check
-2(-1)+6(-5)=-28
2-30=-28... (-a)(-b)=ab
-28=-28
Hope it helps!
Answer:
Volume = 66 cm³
Step-by-step explanation:
Area of the oblique triangular prism = Area of the triangular base × Vertical height from the base
From the figure attached,
Area of the triangular base = ![\frac{1}{2}(\text{Base})(\text{Height of the right triangle})](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28%5Ctext%7BBase%7D%29%28%5Ctext%7BHeight%20of%20the%20right%20triangle%7D%29)
=
= 6 cm²
Vertical height of the given oblique prism = 11 cm
Volume of the given oblique prism = 6 × 11
= 66 cm³
Answer:
Joe mama
Step-by-step explanation:
The Food Pyramid
Answer:
y= -3+2
Step-by-step explanation:
F^-1(x)= x/9 + 1/3
To find this, just interchange the variables and solve for y.
y=9x-3
x=9y-3
x+3=9y
divide by nine